Multiinterval Sturm–Liouville boundary-value problems with distributional potentials - Goriunov, A.S. (Доповіді НАН України, 2014)
We study the multi-interval boundary-value Sturm–Liouville problems with distributional potentials. For the corresponding symmetric operators boundary triplets are found and the constructive descriptions of all self-adjoint, maximal dissipative and maximal accumulative extensions and generalized resolvents in terms of homogeneous boundary conditions are given. It is shown that all real maximal dissipative and maximal accumulative extensions are self-adjoint and all such extensions are described.